The effect of digital technology on students' reading Behavior - Pido, Nur Wahidah Thayib; Sujitno, Fatrah Dwik Cantika (Journal of English Teaching and Linguistic Issues (JETLI), 2022)
The study discusses the effect that technology can have on a student's reading behavior. Where students now a day spend a lot of time with cell phones. Rapid advances in telecommunications technology, media and information technologies and the widespread development of global information infrastructure transform learning and reading patterns into global paradigms. It was this paradigm that became dominant and effectively became involved in the revolution of information networks, which would later determine the future of national welfare. Technology, however, remains the initial hypothesis before research is carried out. In this method is use qualitative method. Study using qualitative method provided a comprehensive and clear picture of the social situations studied, comparative events from one social to another or from one time to another; or be able to find patterns of connections between certain aspects and others, and be able to find hypotheses and theories. In a study that described the work done by 12 respondents. Based on Moleong, the aim of the writer is to examine how the student's behavior, habits, and perceptions of how technology affects reading habits for them. The purpose of this study is to know whether technology has a major impact on student reading behavior. The results of this study indicate that technology had a positive impact on the interest in reading students, but most students prefer reading nonfiction rather than reading lessons. And technology can has a negative impact on the student as student interest is distracted and they are sedated with the modern technological sophistication of gadgets.